Clinical-laboratory and instrument indices of the thyroid gland state after surgical treatment of tumors of the chiasmatic-cellar region - Ya. A. Kan; M. G. Zhestikova; S. M. Bryzgalina; N. P. Shakhvorost (Бюллетень сибирской медицины)
Hypopituitarism is often developed in the result of operative treatment of tumours in chiasmal-cellular area. One of frequent indications of hypophysis’ deficit is decreasing of product of thyroid-stimulating hormone (TSH) that leads to deficit of thyroid hormones. Most patients, who had been operated in terms of tumours of chiasmal-cellular area, have normal volume and structure of thyroid gland in the background of decreased level of free thyroxine and absence of increasing of level of TSH on the principle of feedback, it indicates to the secondary character of destruction of thyroid gland. Patients operated in terms of craniopharyngioma and somatoprolactinoma more often have secondary hypothyroidism. A high per cent of fibrotic changes of tissue of thyroid gland in patients operated in terms of prolactinoma is explain by autoimmune thyroiditis in anamnesis.